Peran OJK Dalam Mendorong Pertumbuhan Keuangan Syariah Di Daerah - Amalia, Faridha; Maghfur, Ifdlolul; Syu’aibi, Mukhsinin (Kartika: Jurnal Studi Keislaman, 2025)
The Financial Services Authority (Otoritas Jasa Keuangan, OJK) plays a strategic role in supervising and promoting the growth of the Islamic financial sector in Indonesia, including in regions that are not national economic centers. This study aims to analyze the impact of OJK’s policies on the growth of Islamic financial products, particularly Hajj savings, at Bank Muamalat’s Pasuruan Sub-Branch Office (Kantor Cabang Pembantu, KCP). The research adopts a qualitative descriptive approach, with primary data obtained through in-depth interviews and direct observations at Bank Muamalat KCP Pasuruan. Secondary data were drawn from policy documents and relevant literature. The findings reveal that OJK’s policies have successfully created a conducive business climate for the development of Islamic financial institutions at the regional level by providing clear regulations, effective supervision, and support for innovative products that comply with sharia principles. This success is further reinforced by the synergy between the formal sector, such as Islamic banking, and social communities that serve as the customer base, thereby expanding outreach and enhancing public literacy in Islamic finance. The study concludes that OJK’s policies not only ensure regulatory compliance but also contribute to strengthening the role of Islamic finance as a driving force for regional economic development